Factors Influencing The Incidence of Loss To Follow-Up Treatment In Drug-Resistant Tuberculosis Patients - Almira Dalimunthe; Bintang Yinke Magdalena Sinaga; Parluhutan Siagian; Rina Amelia (International Journal of Health and Pharmaceutical (IJHP), 2025)
Drug-resistant tuberculosis (DR-TB) represents a significant global health challenge with Indonesia ranking second highest for pulmonary TB cases. Treatment adherence in DR-TB patients is influenced by multiple interacting factors requiring systematic investigation to identify independent risk determinants. This descriptive analytical cross-sectional study assessed associations between independent variables and loss to follow-up treatment outcomes in DR-TB patients at Adam Malik Hospital, Medan, from May to November 2024. A purposive sampling strategy enrolled 104 bacteriologically confirmed DR-TB patients comprising 34 loss to follow-up cases and 70 treatment completers. Data collection utilized validated questionnaires assessing attitudes toward treatment, perceived social support, and healthcare service quality. Statistical analysis employed chi-squared testing for bivariate associations and multiple logistic regression for multivariate analysis with significance level p<0.05. Results demonstrated that 85.3% of loss to follow-up patients experienced low to moderate social support, 67.6% held poor treatment attitudes, and 64.7% perceived insufficient healthcare services. Bivariate analysis revealed significant associations between education (PR=4.13; p=0.023), attitudes (PR=6.04; p<0.001), social support (PR=14.50; p<0.001), and healthcare services (PR=5.72; p<0.001) with treatment discontinuation. Multivariate analysis identified three independent risk factors: low to moderate social support emerging as the predominant determinant (PR=14.01; 95% CI=4.26–46.02; p<0.001), followed by inadequate healthcare services (PR=3.33; 95% CI=1.18–9.43; p=0.023), while unemployment showed protective effect (PR=0.315; p=0.045). This investigation concludes that social support constitutes the principal modifiable risk factor for loss to follow-up treatment in DR-TB patients, necessitating implementation of family-based psychosocial interventions and quality healthcare service improvements to sustain treatment adherence during the challenging 20-month therapeutic regimen.